The Fate of Kristijonas Donelaitis’s Epic Formulae in the Translations of The Seasons into Russian - Dilytė, Dalia (Senoji Lietuvos literatūra, 2024)
The article is focused on one aspect of David Brodsky’s and Sergei Isaev’s translations of Kristijonas Donelaitis’s Metai (The Seasons) into Russian: the rendition of the epic formulae. In an epic work, formulae play an important role. Repetitions of lines and word combinations are not only certain signals that bind the text together; more importantly, the formulae impart the impression of permanence, preservation of tradition, and solidity to an epic text.An examination of the translations of the epic formulae reveals that the translators of The Seasons into Russian struggled with them. No effort to convey the structure of Donelaitis’s formulae in a consistent and coherent way was discerned in these translations. Both translators alternate, in various ways, between the short forms of these word combinations and between the key words.
Keywords: epic; epic formula; Donelaitis